A NATURAL CHEMO-MECHANICAL CARIES REMOVAL AGENT- PAPACARIE - R.PRADEEP KUMAR., (International Journal of Pharma and Bio Sciences, 2014)
Researchers are more interested in developing alternative methods for cavity preparation and caries removal for several years. The chemo-mechanical caries removal is a non-invasive technique for caries removal which aims at the elimination of infected dentin. Papacarie is an emerging chemo-mechanical caries removal agent which on interaction with the exposed collagen causes dissolution of dentin minerals and makes the dentin softer and hence facilitates removal of caries. It has bactericidal, bacteriostatic and anti- inflammatory characteristics. It is extracted from the latex of leaves and fruits of the adult green papaya (Carica papaya). Papain can safely be used as a method for caries removal when employed along with conventional adhesive systems. With the available reference the chemo-mechanical caries removal has so far been the most promising method as alternative treatment procedures especially for children, anxious and medically compromised patients.